2005
DOI: 10.1016/s1808-8694(15)31273-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and radiograph study of the persistence of Foramen of Huschke

Abstract: The results proved that the foramen of Huschke can be observed in skulls submitted to contrast using radiographic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Moreno et al 13 identified and located the foramen of Huschke using contrast material through extraoral Figure 3 There is no foramen tympanicum in both sides, 1 mm with thickness sagittal slice, flat panel detector-based cone beam CT scan (white arrow) Figure 4 There is no foramen tympanicum in both sides, 0.5 mm with thickness axial slice, flat panel detector-based cone beam CT scan (white arrow) radiographs, such as panoramic, submental vertex and corrected sagittal linear TMJ tomograms, in four skulls. They reported that linear tomography provides the best results to visualize the foramen of Huschke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreno et al 13 identified and located the foramen of Huschke using contrast material through extraoral Figure 3 There is no foramen tympanicum in both sides, 1 mm with thickness sagittal slice, flat panel detector-based cone beam CT scan (white arrow) Figure 4 There is no foramen tympanicum in both sides, 0.5 mm with thickness axial slice, flat panel detector-based cone beam CT scan (white arrow) radiographs, such as panoramic, submental vertex and corrected sagittal linear TMJ tomograms, in four skulls. They reported that linear tomography provides the best results to visualize the foramen of Huschke.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that linear tomography provides the best results to visualize the foramen of Huschke. 13 CBCT is a relatively new 3D imaging technique requiring a significantly lower radiation dose than conventional CT. CBCT differs from conventional CT imaging in that the whole volume of data is acquired in the course of a single sweep of the scanner. The exposure time with CBCT scanners is typically less than 20 s and reconstruction of the image takes less than 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,23 Several studies of detection of this anatomical variation, using conventional CT and cadaver studies, have been published. 1,2,10,26 However, only 1 study has been conducted on CBCT imaging, 1 but to our knowledge, no attempt has been made to study the visualization of foramen tympanicum according to orthodontic malocclusions using CBCT imaging. Hence, it was considered worthwhile to assess the occurrence and location of the foramen tympanicum according to orthodontic malocclusions and sex in a Turkish sample using CBCT.…”
mentioning
confidence: 99%
“…[10] It was most evident by linear tomography. However, being a rather obsolete technique, they recommended CT as the best technique to visualize the foramen.…”
Section: Discussionmentioning
confidence: 98%